Acesso e memória: a informação nos arquivos das arquidioceses da Paraíba e de Olinda/Recife - Queiroz, Anna Carla Silva de (2011)
The present study aimed at providing a comparative study of the archives of the Archdiocese of Paraíba and Olinda / Recife in relation to the construction of memory and access to information. Its importance stems from a rich volume mass of documents, since the Catholic Church, in periods prior to the Proclamation of the Republic, produced records of birth, baptism, property records, among others. During this period, the regime in force in Brazil of patronage in which the Church was tied to the state, producing and accumulating a vast production of cultural, social, economic and political results of the archival point of view, a merging of civil and ecclesiastical information. The methodology consisted of an analysis of files, from the recommendations of CONARQ, focusing on the document types and media types, physical structure, projects and coordination of activities, internal regulations, budget, cataloging, accessibility, human resources. The survey was conducted from a structured questionnaire, as well as the application of simple interviews to notaries responsible for the archive. The results of the research is leading us to infer that there is contrast between the collections since the collection of Paraiba is organized, however the Pernambuco in this precarious situation. Thus it was observed that only the first case the file is within the guidelines proposed by the Pontifical Commission for the Cultural Patrimony of the Church.